Perceived Competition and Process of Care in Rural China - Lin X; Jian W; Yip W; Pan J (Risk Management and Healthcare Policy, 2020)
Xiaojun Lin,1,2 Weiyan Jian,3 Winnie Yip,4 Jay Pan1,2 1West China School of Public Health and West China Fourth Hospital, Sichuan University, Chengdu, People’s Republic of China; 2West China Research Center for Rural Health Development, Sichuan University, Chengdu, People’s Republic of China; 3Department of Health Policy and Management, School of Public Health, Peking University Health Science Center, Beijing, People’s Republic of China; 4Department of Global Health and Population, Harvard T.H. Chan School of Public Health, Boston, MA, USACorrespondence: Jay PanWest China School of Public Health and West China Fourth Hospital, Sichuan University, No. 17, Section 3, Ren Min Nan Road, Chengdu 610041, Sichuan, People’s Republic of ChinaTel +86 28 8550 1096Fax +86 28 8550 1528Email panjie.jay@scu.edu.cnPurpose: Although there is much debate about the effect of hospital competition on healthcare quality, its impact on the process of care remains unclear. This study aimed to determine whether hospital competition improves the process of care in rural China.Patients and Methods: The county hospital questionnaire survey data and the randomly sampled medical records of bacterial pneumonia patients in 2015 in rural area of Guizhou, China, were used in this study. The processes of care for bacterial pneumonia were measured by the following three measures: 1) oxygenation assessment, 2) antibiotic treatment, and 3) first antibiotic treatment within 6 hours after admission. Hospital competition was measured by asking hospital directors to rate the competition pressure they perceive from other hospitals. Multivariate logistic regression models were employed to determine the relationship between perceived competition and the processes of care for patients with bacterial pneumonia.Results: A total of 2167 bacterial pneumonia patients from 24 county hospitals in 2015 were included in our study. Our results suggested that the likelihood of receiving antibiotic treatment and first antibiotic treatment within 6 hours after admission was significantly higher in the hospitals perceiving higher competition pressure. However, no significant relationship was found between perceived competition and oxygenation assessment for patients with bacterial pneumonia.Conclusion: This study revealed the role of perceived competition in improving the process of care under the fee-for-service payment system and provided empirical evidence to support the pro-competition policies in China’s new round of national healthcare reform.Keywords: perceived competition, market concentration, process of care, pneumonia, quality, healthcare reform